Economics of Cereal and Vegetable Crops under Organic and Conventional Production Systems in Nepal - Panta, Hari Krishna (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2022)
Chemical fertilizers have a great contribution in agricultural production in Nepal. So far, only about 50% of total demand for chemical fertilizer has been met. Government has been providing subsidy protecting farmers from high cost of imported fertilizers. However, the supply of chemical fertilizer is not smoothened as expected. With the tragedy of different problems of fertilizer importation, distribution, and use, stakeholders have started thinking organic production as an alternative of conventional agriculture in Nepal. However, transforming from conventional to organic agriculture is questioned because of conflicting finding regarding the real profitability of organic production technique. Responding to the situation, a study was conducted to analyze comparative economics of organic and conventional production system using gross margin and cost-benefit analysis covering five selected crops (rice, tomato, potato, bitter gourd, and cauliflower). The study was carried out by random sampling of 250 producers where 200 were conventional and 50 organic farms from five rural/municipalities of Sindhupalchhok, Dhading, Gorkha, Chitwan, and Rupandehi districts. Estimated gross margins and benefit cost analysis indicated that organic products are as profitable as conventional products except in tomato. In overall, vegetables were more profitable than cereals both for organic and conventional systems.